Exported growth hypothesis: empirical evidence from selected Sub-Saharan African countries - Chia, Yee Ee (2015)
The objective of this study ls to examine the validity of Export-Led Growth (ELG) hypothesis in selected Sub-Saharan African (SSA) countries for the period from 1985 to 2014. A new generation panel data approach is applied such as panel unit root, panel cointegration, Fully Modified OLS (FMOLS) and Dynamic Ordinary Least Square (DOLS). The empiric.al findings revealed that the panel unit root is stationary after the first difference and presents a CX>integration. After the confirmation of panel cointegration, there exists a long-run relationship between exports and growth based on FMOLS and DOLS results. FMOLS and DOLS estimation showed a positive impact of investment, government expenditure and exports on the economic growth. Hence, the findings proved that export-oriented growth strategy is valid in the SSA countries.